PENGARUH PENGHINDARAN PAJAK DAN BIAYA AGENSI TERHADAP NILAI PERUSAHAAN DENGAN TRANSPARANSI SEBAGAI VARIABEL PEMODERASI - sekar, laras; Sadewa, Prima (Publika Citra Media, 2024)
This research aims to analyze the effect of tax avoidance and agency costs on company value with transparency as a moderating variable. The type of research used in this research is quantitative. The data source used is secondary data, namely annual financial reports obtained from the Indonesia Stock Exchange (BEI). The population used in this research is non-cyclical industrial sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 period. The sample selection technique used purposive sampling technique and obtained 19 companies over 5 years with a total sample data obtained of 95 sample data. The results of this study indicate that tax avoidance and agency costs simultaneously have no effect on firm value, tax avoidance has no effect on firm value, agency costs have no effect on firm value, tax avoidance has no effect on firm value with transparency as a moderating variable, while agency costs influence on company value with transparency as a moderating variable.